THE CORRELATION BETWEEN INFERIORITY COMPLEX AND SOCIAL INTERACTIONS IN ADOLESCENTS: - - Winda Prastika Johan; Haris Herdiansyah; DINDIN DIMYATI (Fakultas Komunikasi, Sastra, dan Bahasa, 2022)
Although inferiority complex may have significant impacts on social interactions, adolescents seem to be unaware or dismiss problems caused by inferiority complex. Thus, investigating inferiority complex and its relationship with social interactions in adolescents may provide more insights on the impacts of inferiority complex toward adolescents. The present study aims to investigate the correlation between inferiority complex and social interactions in adolescents. The present study applies a correlational research. Data is collected using a convenience sampling technique by delivering an online questionnaire to 140 adolescents aged 10 to 19 years old. The findings of the present study show a strong and positive relationship between inferiority complex and social interaction, with a Pearson correlation value of 0.705. Implications and suggestions for further studies are also discussed.